Strategi Pengembangan Home Industry Era New Normal Pandemi Covid 19 Dalam Meningkatkan Pendapatan (Studi Kasus Kelompok Usaha Bersama (KUBE) â€œArjanjangâ€ Desa Selebung Ketangga, Kabupaten Lombok Timur) - Tati Atmayanti; Baiq Dewi Lita Andiana; Vici Handalusia Husni (Universitas Hamzanwadi, 2021)
Community empowerment efforts through UMKM are a form of poverty eradication. One of them is by developing a home industry or home industry by forming a joint business group (KUBE). The Covid-19 pandemic has an impact on an economic downturn which has resulted in a decline in income and development of MSMEs, including in NTB. This study aims to formulate a home industry development strategy in the new normal era of the Covid-19 pandemic, in order to increase the income of KUBE